Exploring the formation of adiabatic shear band in aluminum alloy for aircraft structures: material properties and structural performance - Manar G.; Bakar M.S.A.; Saad M.R.M.; Rahman M.R.A. (Elsevier, 2025)
This chapter introduces a comprehensive analysis of the thermal and mechanical properties of two considered aluminum alloys, namely AA2024 and AA7175. A thorough experimental investigation encompassing compression, tension, and shear-compression tests was conducted to explore the individual and combined impacts of strain rate, strain, loading, and temperature across a wide array of loading conditions. Moreover, the influence of stress triaxiality was addressed by conducting tests on a hat-shaped specimen and a notched tension specimen. The findings indicate that AA7175 exhibits greater strength compared to AA2024 and that both materials demonstrate minimal sensitivity to strain rate but significant temperature dependence. Furthermore, AA7175 experiences premature failure due to adiabatic shear banding when exposed to high-strain rate loading at low-stress triaxiality levels. Under positive stress triaxiality conditions, a critical temperature threshold is identified, beyond which AA7175 failure occurs through microvoids, while below this threshold, failure results from microshear decohesion. ? 2025 Elsevier Inc. All rights reserved.